Perlindungan Hukum Lagu Yang Diaransemen Ulang Berdasarkan Undang-Undang Hak Cipta - Destiara Meisita Fafitrasari; Kholis Roisah; Mujiono Hafidh Prasetyo (Magister Kenotariatan Universitas Diponegoro, 2021)
The case of infringement of music copyrights uploaded through the Youtube website platform between Nagaswara Music Publisherindo resulted in a lawsuit filed by Nagaswara for alleged copyright infringement on the song with the title